PERBEDAAN HASIL BELAJAR EKONOMI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW DENGAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) SISWA KELAS XI IPS SMA NEGERI 14 MEDAN T.A 2022/2023 - Herma Yunita; Cita Ayni Putri Silalahi (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This research is a quantitative study that aims to see differences in economic learning outcomes using the Jigsaw cooperative learning model whit the Numbered Head Together (NHT) learning model. The population in this study were students of class XI IPS 1 and 2, totaling 72 students. The sampling technique is total sampling where all members of the population are sampled. The research results obtained tcount = 6,68 and ttabel = 1,665, where tcount (6,68) ? ttable (1,665).So it can be concluded that there are differences in student economics learning outcomes using the Jigsaw learning model using the Numbered Head Together (NHT) learning model.